Insights of acupuncture in modulating gut microbiota in stroke treatment - Hang Xing; Wan-juan Lin; Wen-long Hu; Juan-shu Cao; Li-yan Cui; Wen Lyu; Hong-kun Zhu; Ai-jun Wu; Qiu-xia Xu; Yan Zhao; Sheng-yong Bao (Frontiers in Neurology)
Stroke, an acute neurological disorder caused by the interruption of cerebral blood flow, is the second leading cause of death and a major contributor to long-term disability worldwide. Recent research has increasingly highlighted the role of gut microbiota in stroke recovery. Post-stroke gut microbiota dysbiosis, characterized by an imbalance in microbial composition, exacerbates neuroinflammation and neuronal injury. Restoring the balance of the gut microbiome may facilitate neurological recovery. Acupuncture, a traditional therapeutic modality, has shown potential in stroke rehabilitation. Evidence suggests that acupuncture modulates gut microbiota composition, restores gut barrier integrity, and reduces endotoxin translocation into the bloodstream, which collectively reduces systemic inflammation and alleviates neurological damage. Additionally, acupuncture may influence immune responses through the gut-brain axis, a bidirectional communication system between the gut and brain, thereby suppressing neuroinflammation and promoting neuronal repair. Despite these promising findings, current evidence is limited by methodological inconsistencies, including variability in acupuncture protocols and heterogeneous patient populations, which may confound result interpretation. The precise mechanisms underlying acupuncture's modulation of gut microbiota and its role in stroke recovery remain unclear. Future studies should adopt standardized protocols and larger sample sizes to improve reproducibility, validate these findings, explore the molecular pathways involved, and determine the clinical efficacy of acupuncture in stroke rehabilitation.